Proyecto de factibilidad para la creación de una empresa productora de pasta de maní en el cantón Paltas, provincia de Loja. - Macas Caraguay, Jhon Alexander (2024)
The objective of the Curricular Integration Project titled 'Feasibility project for the creation of a peanut paste production company in the canton of Paltas, province of Loja' is to determine the technical, economic, and financial feasibility for its implementation. The research began with a market study, which resulted in an effective demand of 98% and an unsatisfied demand of 84,776 pounds or 38,467.61 kilograms at the time of the study. The technical analysis helped determine the optimal macro and micro location for the company, which is on Moras Street in the San José neighborhood of Catacocha Parish, Paltas Canton, Loja Province. Additionally, the analysis determined the type of company to established and the structural and functional organization chart that employees must follow to conduct their activities. In the economic and financial realm, the initial capital of $8,376.02 will contributed the Owner Manager of the company, with an additional $30,000.00 in external financing requested from the Central Bank of Ecuador, known as 'BANECUADOR', resulting in a total investment of $38,376.02. The financial evaluation yielded a net present value of $89,376.22, an internal rate of return of 12.50%, a benefit-cost ratio of 1.53, and a capital recovery period of 2 years, 7 months, and 14 days. The sensitivity analysis indicates that the project can withstand a 25% increase in costs and a 20% decrease in income. Based on the above-mentioned aspects, the establishment of a company to produce peanut paste is feasible and the financial evaluation indicators are positive and guarantee profitability. Therefore, the implementation this plan is feasible.